DNA‐Binding and Anticancer Activity of Pyrene‐Imidazolium Derivatives. Issue 21 (21st December 2016) - Bonsignore, Riccardo; Notaro, Antonietta; Salvo, Anna Maria Pia; Spinello, Angelo; Fiasconaro, Giuseppe; Terenzi, Alessio; Giacalone, Francesco; Keppler, Bernhard K.; Giuliano, Michela; Gruttadauria, Michelangelo; Barone, Giampaolo
Abstract: DNA‐binding investigations showed that two different derivatives endowed with pyrene and imidazolium moieties, 1 and2, strongly bind both double‐stranded DNA and telomeric sequences in G‐quadruplex (G4) conformation. The values of the DNA‐binding constants indicate that1 and2 show preferential affinity for G4‐DNA, of about one and two orders of magnitude, respectively. Moreover, 1 and2 inhibit short and long‐term proliferation of breast cancer cell lines in a time‐ and dose‐dependent fashion. Remarkably, senescence assays indicate that telomeric G4‐DNA is a possible biotarget for the cytotoxic activity of2 . Molecular dynamics simulations suggest that the stronger binding of2 with G4‐DNA and the related senescence induction, are a consequence of additional edge‐to‐face interactions with a base in the TTA loop. Abstract : A bispyreneimidazolium derivative strongly binds G‐quadruplex DNA by stacking and face‐to‐edge interactions, inducing senescence in cancer cell lines